The Utilization of Pediatric Hip Spica Tables Among Orthopedic Surgeons: Locally Customized versus Company-Manufactured (Cross-Sectional Study) - Alomran AK; Almulhim H; Alabdulqader S; Almutairi DS; Alrusayyis DF; Althwaiqb SA; Alumran A (Journal of Multidisciplinary Healthcare, 2023)
Ammar K Alomran,1 Hadeel Almulhim,2 Shahad Alabdulqader,2 Danah S Almutairi,2 Danah F Alrusayyis,2 Sarah A Althwaiqb,2 Arwa Alumran3 1Orthopedics Department, Imam Abdulrahman bin Faisal University, College of Medicine, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Saudi Arabia; 3Health Information Management and Technology Department, Imam Abdulrahman bin Faisal University, College of Public Health, Dammam, Saudi ArabiaCorrespondence: Hadeel Almulhim, Tel +966501407070, Email 2170006025@iau.edu.saBackground: Hip spica tables are widely used among pediatric orthopedic surgeons to maintain the hip position during cast application and drying processes for a better outcome. Locally customized spica tables can be a significant concern if their limitations significantly interfere with the quality of care.Objective: This study aims to explore the current practice of pediatric hip spica table application among hospitals in the GCC countries and report comprehensive data that help surgeons enhance their practice.Methods: This is a cross-sectional study on pediatric orthopedic surgeons using a self-administered Online Questionnaire. The respondents were grouped as those using locally customized tables, where further information about the material and characteristics were collected, and those using company manufactured tables. Both groups answered analytical questions related to their current practice of hip spica tables.Results: Sixty-three surgeons completed the survey. More than half the physicians in this study are using locally customized spica tables (n= 41, 65%). Compared to company-manufactured tables, locally customized tables were associated with a higher rate of difficulties when taking an X-ray, when the patient weighs more than 50.0 kg, and with anesthesia, although not statistically significant.Conclusion: Obtaining a good quality spica table at a suitable price is a primary obstacle pediatric orthopedic surgeons face. This study shows no statistically significant difference between locally customized and company-manufactured tables regarding the outcomes and that spica tables have room for development to optimize their utilization.Keywords: spica tables, pediatric orthopedics, spica cast, developmental dysplasia of the Hip, DDH, fractures